Los Títeres como recurso para promover el hábito de la lectura en niños de 5 años - Buitrón Olivo, Olivia Estefanía (2022)
The present investigation was given in front of the problem evidenced in the teachers of the high school level, who do not use adequate didactic resources for the development of reading habits, therefore, the objective of the present investigation is to analyze the importance of the use of puppets in the development of reading habits to improve the reading processes in children of the first year of basic education of the Ramón Barba Naranjo Educational Unit, consequently, we proceeded to review the theoretical references that support the importance of the use of puppets and the development of reading habits, Theoretical references that support the importance of the use of puppets and the development of reading habits were reviewed, as well as the elaboration of techniques and instruments for the collection of information to diagnose if the teachers of the first year of basic education use puppets as a didactic resource for the development of reading habits and also if parents promote reading habits at home, highlighting in the results obtained the importance of the use of puppets. The methodology used has a hybrid approach of bibliographic documentary and field modality. Its type of research is Descriptive, following the Deductive Method, whose collection techniques correspond to three tools: a survey of teachers and parents and an interview with the institution's rector. Thus, it was found that the use of puppets benefits the development of oral language in infants, favoring their creativity and good reading habits. Also, all the teachers of the institution apply techniques to develop the children's language and the use of puppets. Finally, it is considered that all teachers and parents should use puppets to promote proper reading habits both at home and in school. They are the current project feasible and of significant social impact in improving the reading process within the teaching and learning of the first year of basic education.